2017
DOI: 10.1016/j.jiph.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of genes responsible for macrolide resistance among Streptococcus pneumoniae isolated in North Lebanon

Abstract: In recent years, the increased use of macrolides was linked with the emergence of resistance Streptococcus pneumoniae worldwide. The main aim of this study was to determine the prevalence of S. pneumoniae resistant to macrolides and to identify the macrolide resistance genotypes among clinical isolates collected in North Lebanon. Disk diffusion susceptibility method was performed for 132 strains of S. pneumoniae isolated over a period of 5 years in North Lebanon. Polymerase Chain Reaction followed by pyroseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…In agreement with this finding, other studies in the Turkey, China and Taiwan showed that the ermB gene was the most frequent macrolide resistance determinant. while the most common resistance gene in the Canada and United States was mefA/E gene [20,21]. In this study the rate of co resistance related to ermB and mefA/E gens was found in 23% of isolates which accordance with a report from Turkey (20%) [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with this finding, other studies in the Turkey, China and Taiwan showed that the ermB gene was the most frequent macrolide resistance determinant. while the most common resistance gene in the Canada and United States was mefA/E gene [20,21]. In this study the rate of co resistance related to ermB and mefA/E gens was found in 23% of isolates which accordance with a report from Turkey (20%) [20].…”
Section: Discussionsupporting
confidence: 89%
“…As for frequency of double resistance to erythromycin and clindamycin has been spread globally. The high prevalence of dual resistance in S. pneumoniae was found in South Korea and South Africa [5,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, two studies conducted in Ethiopia and Pakistan showed high level of resistance to ciprofloxacin, with 16.2% and 59% respectively [13,20]. Indeed, our generated data are in accordance with recent national studies reporting an increased level of antimicrobial resistance among infectious bacterial agents, a striking low level of antibiotic awareness among Lebanese population, a spread of counterfeit medicines, and a misuse of antibiotics in Lebanon [6][7][8][9][10][11][26][27][28][29][30][31][32]. Even if this study provides useful information for physicians to develop effective empirical antibiotic treatment for M. catarrhalis infections, we advise to pay attention to this prominent issue and we recommend the implementation of reliable identification and antibiotic susceptibility testing in routine laboratory diagnostics to guide appropriate treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the current study, which was carried out in line with similar studies conducted in Germany (9), the UK (29), and Iran (30), confirmed that most erythromycin-resistant samples harbored mefA gene. A study by Kargar et al showed a significant relationship between erythromycin resistance and the frequency of mefA gene harboring (31); also, D'Ercole et al screened 124 S. pyogenes isolates for the presence of mef (A) and the frequency was reported as 25.8% (32); while in North Lebanon only 2.2% of isolates harbored mefA gene (33). These findings revealed that the prevalence of resistant bacteria harboring mef gene is rising in most countries.…”
Section: Discussionmentioning
confidence: 99%